Al-Qur’an sebagai Sumber Hukum Al-Qur’an sebagai Landasan Utama dalam Sistem Hukum Islam - Siti Naila Aziba; Keathy Abrillie Zhumi; Teguh Purbowo; Syahrul Alif Rozaq (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Qur'an is the main foundation in the Islamic legal system which serves as a guideline regulate the lives of individuals and society. This research is motivated by its importance understand the position of the Qur'an as a primary source of law that underlies development legal rules in Islam, both those of worship and muamalah. Objective This research is to examine in depth how the Qur'an becomes a reference The main aspects of the Islamic legal system and how they are applied in the contemporary era. Method The research used is qualitative-descriptive with a literature study approach includes analysis of Al-Qur'an verses, interpretations of ulama, as well as the study of legal-related documents Islam. The research results show that the Qur'an does not only provide principles universal law, but also provides a mechanism for interpretation through ijtihad and adaptation to the socio-cultural context. This makes the Qur'an relevant in guiding the drafting of Islamic law that is fair and flexible to answer challenges era. This research emphasizes the central role of the Koran in building a legal system which is in accordance with the values ​​of justice and the benefit of the people.